2015
DOI: 10.1002/j.1556-6676.2015.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analytic Review of Child‐Centered Play Therapy Approaches

Abstract: The authors explored the overall effectiveness of child‐centered play therapy (CCPT) approaches through a meta‐analytic review of 52 controlled outcome studies between 1995 and 2010. Hierarchical linear modeling techniques estimated a statistically significant moderate treatment effect size (.47) for CCPT, as well as statistically significant relationships between effect size and study characteristics, including child's age, child's ethnicity, caregiver involvement, treatment integrity, publication status, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
175
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(223 citation statements)
references
References 41 publications
14
175
1
10
Order By: Relevance
“…CCPT is identified as the most popular theoretical approach to play therapy (Lambert et al, 2005). Additionally, metaanalyses have reported positive and meaningful effects for children who participate in CCPT (Bratton, Ray, Rhine & Jones, 2005;Lin & Bratton, 2015;Ray, Armstrong, Balkin & Jayne, 2015).…”
Section: Person-centered Approach To Anxietymentioning
confidence: 98%
“…CCPT is identified as the most popular theoretical approach to play therapy (Lambert et al, 2005). Additionally, metaanalyses have reported positive and meaningful effects for children who participate in CCPT (Bratton, Ray, Rhine & Jones, 2005;Lin & Bratton, 2015;Ray, Armstrong, Balkin & Jayne, 2015).…”
Section: Person-centered Approach To Anxietymentioning
confidence: 98%
“…Empirical studies have shown the efficacy of play therapy with a variety of childhood emotional and behavioral concerns (Bratton, Ray, Rhine, & Jones, 2005;Lin & Bratton, 2015;Wang, Jang, Lian, & Wang, 2006). Specifically, Ray, Armstrong, Balkin, and Jayne (2015) reviewed studies addressing child centered play therapy in elementary schools and found it to be an efficacious treatment for internalizing problems, externalizing problems, total problems, self-efficacy, academic, and other concerns.…”
Section: Play Therapy and Internalizing And Externalizing Behaviorsmentioning
confidence: 99%
“…A more recent meta-analytic review by Lin and Bratton (2015) explored 52 controlled outcome studies between 1995 and 2010 on child-centered play therapy (CCPT) approaches.…”
Section: Child-centred Play Therapymentioning
confidence: 99%
“…CCPT is different from other theoretical models by the determined belief that children inherently strive toward personal growth and maturity, as well as having capacity for self-directed healing (Lin & Bratton, 2015). This meta-analytic review included ethnicity as a part of the study characteristics.…”
Section: Child-centred Play Therapymentioning
confidence: 99%
See 1 more Smart Citation